The Philosophy Meaning Experimental Music Works “Dreadlocks” - Gede Made Rama Pratama; Rai S I Wayan; I Komang Sudirga (Randwick International of Social Science Journal, 2023)
The purpose of creating the experimental piece of music "Dreadlocks Hair" is to prove that the Rebab can be used as the main instrument in gending. The experimental musical work "Hairlocks Dreadlocks" was created using a creation theory based on local wisdom (Rai S., 2021), which focuses on talent as the principal capital and identity of the work. The process of creating this new musical work uses a creation theory based on local wisdom by developing elements of: (1) talent as the main capital, (2) creativity ability, (3) understanding of local wisdom, (4) concept of work, (5) as a prayer offerings, and (6) visualizing the form of the work. The process of creating this piece of Dreadlocks music is based on the Rebab, namely the "Electric Rebab" instrument. The new innovation in this experimental piece of music lies in the protrusion of the resulting Rebab sound register. The novelty of this experimental piece of music is that the Rebab is able to produce 3 (three) sound colors namely low, medium and high simultaneously in one instrument. The problem: What does Dreadlocks mean in a new piece of music?; What does Dreadlocks mean in a new piece of music? The development of the Rebab instrument which is actualized as the dominant instrument in the experimental musical work "Dreadlocks" is not necessarily interpreted literally, but is interpreted as extramusical or the personification of the creator who views the Rebab instrument as different. The word "hair", in this case, is interpreted as sound-forming elements similar to strings or strings and fine strings on a bowstring. Meanwhile, the creator uses the word "Dreadlocks" as a metaphor to describe the harmonious musical texture, voice register (high, medium, low) and rhythmic patterns contained in this work. Experimental musical piece “Dreadlocks”. contains the meaning of dismantling the established standard, development, preservation, and glorification with a moral message to preserve local wisdom using beraya, dreadlocks aesthetic as a metaphor.